Bahasa Inggris - Aprilianti Dwi Yuntiari; Pujiriyanto (Postgraduate, University of Mataram, 2025)
This research aims to determine the user experience of elementary school teachers in Samarinda City using the SSE application for evaluation learning media in terms of 6 aspects (attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty) as well as the responses, troubles, and feedback from teachers as users. The research uses a mixed method with sequential explanatory design, analyzing quantitative data through the User Evaluation Questionnaire (UEQ) and qualitative data through interviews. The results show that the teachers' experience level for the aspects of attractiveness (1.71), efficiency (1.74), stimulation (1.41), novelty (1.27) are included in the